Partisipasi Masyarakat dalam Pemanfaatan Lahan Pekarangan sebagai Upaya Pengurangan Angka Kemiskinan di Desa Wulungsari Kecamatan Selomerto Kabupaten Wonosobo - Nurul Kurniawati; Kushandajani . (Journal of Politic and Government Studies, 2019)
Community participation is a determining factor in achieving the success of a development program, because the community here acts as the main actor in the implementation of a development program. In Wulungsari Village, it uses land use activities that aim to maximize the use of community land to fulfill the needs of the community. This research aims to find out how community participation both in planning, implementation and evaluation. The approach in this study uses a qualitative approach, the technique of data collection is done by interviews, observation and documentation.The research subjects consisted of the Wulungsari Village people, while the analysis used was qualitative descriptive analysis, The results obtained in this study: (1) The level of community participation in the implementation of land use is arguably good even though not all people expressed their opinions but they also influenced and were involved in decision making (2) Wulungsari Village community participation in terms of good funds , energy, material and thought are also good, even though at the beginning of the implementation of land use there has been no assistance at all from the government but residents voluntarily use their own self-help (3) for the obstacles faced, the need for socialization to increase community motivation.Keywords: Community participation, Land use, Welfare